2018
DOI: 10.1007/s42452-018-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent catalytic property of gold nanoparticle mediated by Justicia adhatoda leaf extract

Abstract: In this contribution, we demonstrate the synthesis of gold nanoparticles (AuNPs) using an entirely green chemistry process. Justicia adhatoda leaf extract used as a bioreductant for the synthesis of AuNPs and its particle sizes are controlled by altering the concentration of metal salt. The optical and morphological properties were studied. We report on the synthesis of stable spherical, well-dispersed colloidal AuNPs (27.1, 33.3 and 46.8 nm) by efficient reducing agents with its mechanisms. The X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 75 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Further, he pointed out that nanofluid are best candidates for heat and mass transfer when these are compared with the other fluids. For applications of nanofluid, see [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Further, he pointed out that nanofluid are best candidates for heat and mass transfer when these are compared with the other fluids. For applications of nanofluid, see [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally unique electrochemical features and high conductivity of AgNPs identifies AgNPs as a good candidate for selective and sensitive monitoring of biomolecules and pharmaceuticals [20][21][22]. Earlier reports have shown that size, shape, and surface features are critical in deciding performance of their so far mentioned catalytic and sensing applications [21][22][23][24][25]. It is reported that the cytotoxicity of AgNPs against diseases like HIV and cancer are also size dependent [2,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this can be found in recent studies applying these principles, which do not take the wider sustainable development goals such as the consequences for ecosystems or livelihoods into consideration, and can thus not be considered to practice sustainable design (e.g. [13,14]). Gopalraj and Kärki [15] do examine the environmental and economic effects of a material but look at recycling and closing the loop to stimulate the circular economy.…”
Section: Literature Leading To Questionnaire Frameworkmentioning
confidence: 99%